Identification of an active miniature inverted‐repeat transposable element mJing in rice - Tang, Yanyan; Ma, Xin; Zhao, Shuangshuang; Xue, Wei; Zheng, Xu; Sun, Hongying; Gu, Ping; Zhu, Zuofeng; Sun, Chuanqing; Liu, Fengxia; Tan, Lubin (The Plant journal : for cell and molecular biology, 2019)
Summary Miniature inverted‐repeat transposable elements (MITEs) are structurally homogeneous non‐autonomous DNA transposons with high copy numbers that play important roles in genome evolution and diversification. Here, we analyzed the rice high‐tillering dwarf (htd) mutant in an advanced backcross population between cultivated and wild rice, and identified an active MITE named miniature Jing (mJing). The mJing element belongs to the PIF/Harbinger superfamily. japonica rice var. Nipponbare and indica var. 93‐11 harbor 72 and 79 mJing family members, respectively, have undergone multiple rounds of amplification bursts during the evolution of Asian cultivated rice (Oryza sativa L.). A heterologous transposition experiment in Arabidopsis thaliana indicated that the autonomous element Jing is likely to have provides the transposase needed for mJing mobilization. We identified 297 mJing insertion sites and their presence/absence polymorphism among 71 rice samples through targeted high‐throughput sequencing. The results showed that the copy number of mJing varies dramatically among Asian cultivated rice (O. sativa), its wild ancestor (O. rufipogon), and African cultivated rice (O. glaberrima) and that some mJing insertions are subject to directional selection. These findings suggest that the amplification and removal of mJing elements have played an important role in rice genome evolution and species diversification. Significance Statement An active MITE in rice, named mJing, was identified by analyzing a spontaneous high‐tillering dwarf mutant in an advanced backcross population between cultivated and wild rice. Through targeted high‐throughput sequencing, we identified 297 mJing insertion sites in rice and found that the copy number of mJing varies dramatically among O. sativa, O. rufipogon, and O. glaberrima, suggesting that the amplification of mJing plays an important role in rice genome evolution.